Land manager attitudes toward management, regeneration, and conservation of Spanish holm oak savannas (dehesas) - Plieninger, T.; Modolell y Mainou, J.; Konold, W. (Landscape and Urban Planning, 2004)
Biological conservation in Spanish dehesas critically depends on the long-term persistence of a holm oak tree layer.Managers of private estates in Cáceres province, Spain, were surveyed about their conservation attitudes and behavior, especially as regards the widespread regeneration failure of oak stands. The aim was to define land-user perspectives on oak conservation in dehesas as basis for the design of suitable oak regeneration programs. Dehesa estates are managed diversely for a variety of goals, with lamb and beef production predominating. Small operations (‘minifundios’) had significantly higher stocking levels than large operations (‘latifundios’). Results suggest that managers strongly appreciate oaks, both for income- and non-income-related motivations like the preservation of real estate value or family tradition. Concern about threats to oak stands like lacking regeneration, oak decline, or conversion in urban areas varied in intensity, but most managers expected major changes for the future. Statistical relationships were established between oak appreciation and socio-economic variables like age, land ownership, years the operation had been owned by the family, and use of oak products. The survey revealed great confusion about existing oak conservation regulations. For long-term support to be assured, policy should orient its efforts toward conservation incentive schemes, environmental education, and technical assistance.
Keywords: Dehesa; Land-use; landowner motivations; Mediterranean; Quercus ilex; rangeland policy